2008
DOI: 10.1308/003588408x242079
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phones, in Combination with a Computer Locator System, Improve the Response Times of Emergency Medical Services in Central London

Abstract: INTRODUCTION The aim of this study was to determine whether mobile phones and mobile phone locating devices are associated with improved ambulance response times in central London. PATIENTS AND METHODS All calls from the London Ambulance Service database since 1999 were analysed. In addition, 100 consecutive patients completed a questionnaire on mobile phone use whilst attending the St Thomas's Hospital Emergency Department in central London. RESULTS Mobile phone use for emergencies in central London has incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…Subsequently, one study has shown that mobile phone locating systems led to faster response time in an urban setting (8). Our study has taken a further step to show that the use of mobile phones in contacting emergency services in life-threatening situations could potentially improve patient survival.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Subsequently, one study has shown that mobile phone locating systems led to faster response time in an urban setting (8). Our study has taken a further step to show that the use of mobile phones in contacting emergency services in life-threatening situations could potentially improve patient survival.…”
Section: Discussionmentioning
confidence: 76%
“…More recently, a UK study showed that mobile phone use for reporting emergencies increased from 5% to 29% of total emergency calls from 1999 to 2004 in London, and the use of mobile phone in combination with a locator system was associated with an improvement in response times to accidents and other emergency situations (8). Automatic provision of location information for emergency calls from mobile phones was not available before September 2003, and accuracy is dependent on the density of network antenna sites (9).…”
Section: Introductionmentioning
confidence: 99%
“…80 The effectiveness of fibrinolytic therapy for acute stroke is highly time sensitive. 81,82 Patient delay in the recognition of stroke and seeking care has been recognized as a major barrier to optimal treatment of acute stroke.…”
Section: Mobile Devices and Strokementioning
confidence: 99%
“…Of the re-allocating ambulances, 23 out of 27 were at existing sites, 4 were allocated to new sites, the average distance increased for 3 sites (by 319m) and decreased for 20 sites (by 630m (Snyder et al, 2007;Stiell et al, 1999). Specifically, several studies have noted the improved survival of patients with a high risk of mortality when the response time was less than 4 to 5 minutes (Blackwell and Kaufman, 2002;Pons et al, 2005) and have sought to improve the response times through enhancing EMS management and relocating ambulance stations (Gossage et al, 2008;Peleg and Pliskin, 2004).…”
Section: Discussionmentioning
confidence: 99%